Optimising Cardiovascular Fitness: A Pretest-Posttest Investigation of Tabata Training on VO2max in Junior Futsal Players - Junaedi, Akhmad; Yunus, Moch.; Taufik, Taufik (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
This research was compiled based on the researcher's goal, namely to find out the effect of Tabata Training on the VO2 max level of futsal players. The research design uses a one-group pretest and posttest design. First of all, a pretest was carried out to determine the initial condition of the athlete's VO2 max and then given treatment in the form of Tabata Training. After that, measurements were retaken to find out the difference in results after being given treatment. The subjects in this study were 15 junior high school male futsal players aged 14-16 years. This research was conducted in 16 meetings for six weeks, three times a week. Data collection techniques through tests. The test instrument to determine VO2max uses a multistage fitness test (MFT). The test results showed that the pretest average was 29.85, while the posttest average was 33.74. These results indicate an increase in the VO2max value of 3.89 (ml/kg/min). Then the data were analysed using a paired sample t-test to answer the research hypothesis. The results show a significance value of 0.000 <0.05. So it can be concluded that Tabata Training significantly increases the VO2 max of futsal players. The limitations of this study are not fully controlled for the research subjects.